Question
upstudy study bank question image url

roblem 1. Let \( y=f(x)=-5 x^{2}+3 x+2 \). Find the Difference opoints) Quotient \( \frac{f(x+h)-f(x)}{h} \) and simplify. Detaild work:

Ask by Rodriguez Moran. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The difference quotient simplifies to \( -10x - 5h + 3 \).

Solution

To find the difference quotient \( \frac{f(x+h) - f(x)}{h} \) for the function \( f(x) = -5x^2 + 3x + 2 \), we will follow these steps: 1. **Calculate \( f(x+h) \)**: We need to substitute \( x+h \) into the function \( f(x) \). \[ f(x+h) = -5(x+h)^2 + 3(x+h) + 2 \] Expanding \( (x+h)^2 \): \[ (x+h)^2 = x^2 + 2xh + h^2 \] Therefore, \[ f(x+h) = -5(x^2 + 2xh + h^2) + 3(x+h) + 2 \] Now, distribute the terms: \[ f(x+h) = -5x^2 - 10xh - 5h^2 + 3x + 3h + 2 \] 2. **Calculate \( f(x+h) - f(x) \)**: Now we need to subtract \( f(x) \) from \( f(x+h) \). \[ f(x) = -5x^2 + 3x + 2 \] Thus, \[ f(x+h) - f(x) = (-5x^2 - 10xh - 5h^2 + 3x + 3h + 2) - (-5x^2 + 3x + 2) \] Simplifying this expression: \[ f(x+h) - f(x) = -10xh - 5h^2 + 3h \] 3. **Form the difference quotient**: Now we can form the difference quotient: \[ \frac{f(x+h) - f(x)}{h} = \frac{-10xh - 5h^2 + 3h}{h} \] We can simplify this by dividing each term by \( h \) (assuming \( h \neq 0 \)): \[ \frac{f(x+h) - f(x)}{h} = -10x - 5h + 3 \] 4. **Final Result**: The simplified form of the difference quotient is: \[ \frac{f(x+h) - f(x)}{h} = -10x - 5h + 3 \] This is the final answer for the difference quotient of the function \( f(x) = -5x^2 + 3x + 2 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To find the difference quotient \( \frac{f(x+h)-f(x)}{h} \) for the function \( f(x) = -5x^2 + 3x + 2 \), we first need to calculate \( f(x+h) \). 1. Compute \( f(x+h) \): \[ f(x+h) = -5(x+h)^2 + 3(x+h) + 2 \] Expanding \( (x+h)^2 \): \[ = -5(x^2 + 2xh + h^2) + 3x + 3h + 2 \] \[ = -5x^2 - 10xh - 5h^2 + 3x + 3h + 2 \] 2. Now subtract \( f(x) \) from \( f(x+h) \): \[ f(x+h) - f(x) = (-5x^2 - 10xh - 5h^2 + 3x + 3h + 2) - (-5x^2 + 3x + 2) \] This simplifies to: \[ -10xh - 5h^2 + 3h \] 3. Now, substitute back into the difference quotient: \[ \frac{f(x+h) - f(x)}{h} = \frac{-10xh - 5h^2 + 3h}{h} \] Factoring out \( h \): \[ = \frac{h(-10x - 5h + 3)}{h} = -10x - 5h + 3 \] So the simplified difference quotient is: \[ -10x - 5h + 3 \]

Related Questions

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy